Patient-specific instrumentation (PSI) Referencing High Tibial Osteotomy Technological Transfer and Education: protocol for a double-blind, randomised controlled trial (PROTECTED HTO Trial) - Mohit Bhandari; Lawrence Chun Man Lau; Elvis Chun Sing Chui; Jason Chi Ho Fan; Gene Chi Wai Man; Yuk Wah Hung; Kevin Ki Wai Ho; Kwong Yin Chung; Samuel Yik Cheung Wan; Jack Wai Wang Chau; Patrick Shu Hang Yung (BMJ Open)
Introduction High tibial osteotomy (HTO) is a treatment of choice for active adult with knee osteoarthritis. With advancement in CT imaging with three-dimensional (3D) model reconstruction, virtual planning and 3D printing, patient-specific instrumentation (PSI) in form of cutting jigs is employed to improve surgical accuracy and outcome of HTO. The aim of this randomised controlled trial (RCT) is to explore the surgical outcomes of HTO for the treatment of medial compartment knee osteoarthritis with or without a 3D printed patient-specific jig.Methods and analysis A double-blind RCT will be conducted with patients and outcome assessors blinded to treatment allocation. This meant that neither the patients nor the outcome assessors would know the actual treatment allocated during the trial. Thirty-six patients with symptomatic medial compartment knee osteoarthritis fulfilling our inclusion criteria will be invited to participate the study. Participants will be randomly allocated to one of two groups (1:1 ratio): operation with 3D printed patient-specific jig or operation without jig. Measurements will be taken before surgery (baseline) and at postoperatively (6, 12 and 24 months). The primary outcome includes radiological accuracy of osteotomy. Secondary outcomes include a change in knee function from baseline to postoperatively as measured by three questionnaires: Knee Society Scores (Knee Scores and Functional Scores), Oxford Knee Scores and pain visual analogue scale (VAS) score.Ethics and dissemination Ethical approval has been obtained from the Joint Chinese University of Hong Kong – New Territories East Cluster Clinical Research Ethics Committee (CREC no. 2019.050), in accordance with the Declaration of Helsinki. The results will be presented at international scientific meetings and through publications in peer-reviewed journals.Trial registration number NCT04000672; Pre-results.